PENINGKATAN MUTU PAUD MELALUI DIGITALISASI: PERAN TEKNOLOGI IFP DALAM MENDUKUNG KOMPETENSI GURU MENUJU PEMBELAJARAN MENDALAM YANG BERKESINAMBUNGAN - Siti Hamidah; Asti eka wijayanti; Erna Yayuk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The increasing demand for early childhood education (PAUD) quality in the digital era necessitates a paradigm shift in pedagogy and technology utilization, addressing the existing quality gap across regions. This study investigates the role of Interactive Flat Panel (IFP) technology adoption as a digital tool to enhance teacher competence and facilitate sustainable deep learning in PAUD. The research problem lies in the challenge of transitioning conventional, surface-level teaching methods into interactive, meaningful, and contextualized deep learning experiences, utilizing new digital infrastructure. This qualitative descriptive research, based on an in-depth literature review and recent policy analysis (2024–2025), identifies the critical role of IFP. The findings indicate that IFP serves two main functions: first, as a technical tool that standardizes and enriches the presentation of digital educational content, improving children's motivation; and second, as a catalyst for pedagogical change, driving teachers toward integrating technology into an inclusive, multi-sensory, and interactive learning process. The successful transition requires continuous, focused teacher capacity building, emphasizing pedagogical digital competence over mere technical skills to design learning experiences that truly prioritize the child's holistic development. This integration ensures that the adoption of IFP contributes to sustained quality improvement and the achievement of deep learning outcomes in early childhood education.